Analysis of Injuries in the Ghanaian Mining Industry and Priority Areas for Research - Eric Stemn (Elsevier, 2019)
Background: Despite improvements in safety performance, the number and severity of mining-related injuries remain high and unacceptable, indicating that further reduction can be achieved. This study examines occupational accident statistics of the Ghanaian mining industry and identifies priority areas, warranting intervention measures and further investigations. Methods: A total of 202 fatal and nonfatal injury reports over a 10-year period were obtained from five mines and the Inspectorate Division of the Minerals Commission of Ghana, and they were analyzed. Results: Results of the analyses show that the involvement of mining equipment, the task being performed, the injury type, and the mechanism of injury remain as priorities. For instance, mining equipment was associated with 85% of all injuries and 90% of all fatalities, with mobile equipment, component/part, and hand tools being the leading equipment types. In addition, mechanics/repairmen, truck operators, and laborers were the most affected ones, and the most dangerous activities included maintenance, operating mobile equipment, and clean up/clearing. Conclusion: Results of this analysis will enable authorities of mines to develop targeted interventions to improve their safety performance. To improve the safety of the mines, further research and prevention efforts are recommended. Keywords: Accident, Injury analysis, Mining, Mining equipment